Asuhan Keperawatan Pada Lelaki Dewasa Dengan Diagnosa Tuberculosis Paru - shanti dafris (Jurnal Ilmiah Cerebral Medika, 2019)
Pulmonary Tuberculosis is a disease caused by Mycobacterium Tuberculosis, which is an aerobic germ that can live mainly in the lungs or in various other organs of the body that have high partial oxygen pressure. The world health organization states that pulmonary tuberculosis (TB) is currently a global threat, nearly one third of the world's population has been infected with TB. This type of research is qualitative research, data collection is done using the assessment method. The results of the assessment are usually shortness of breath, cough with phlegm for more than 2 weeks, cold sweats at night with fever, the general condition of the client is weak and, RR: 28 x / minute, S: 38oC. Diagnosis that appears diagnosis Ineffective airway clearance due to excessive sputum orders. The conclusion of this study is that after nursing care, the diagnosis can be resolved. The hope in the future is to be able to maximize nursing action so that it can provide nursing care so that it can provide optimal nursing care to patients with pulmonary tuberculosis.